Biomechanics in bone regeneration and mechanobiology in osteoblasts: Fundamental concepts and recent progress - Wenbin Cai; Yaya Huo; Yu Liu; Yan Su; Haobo Guo; Lijie Wang; Bin Li; Ting Liang (EngMedicine)
Bone is a hard, dynamically active tissue that continually rebuilds and maintains its mineral balance and structural integrity. Multiple mechanical properties of bone determine its ability to deform and fracture under load, as well as provide stable support and durability during motion. Meanwhile, the mechanical microenvironment within the bone can directly influence bone cells, whose perception of mechanical forces may enhance or inhibit various biological functions. Based on these mechanobiological processes, the mechanical design of biomaterials for bone repair and regeneration is becoming increasingly important. To achieve better clinical outcomes, bone repair materials should be selected based on the characteristics of the materials used in clinical application to achieve better outcomes. This review discusses the types of mechanical loading to which bone is subjected, how osteoblasts respond to such loading and the potential mechanisms involved, and the mechanical design of various biomaterials for bone repair. It then summarizes the progress made in bone-related biomechanical research and provides an outlook for future research efforts.